Medico Legal Issues in Obstetrics and Gynecology - Pradhan, Savana (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To highlight the principles and practicalities of the law and how medical negligence claims are addressed in court. Methods: Literature and legal case search. Results: This review discusses preventative modalities on legal complaints and summarizes the rationale and implementation of key legal standards used to rule medical negligence, namely, the Bolam, Montgomery and Bolitho principles. Practicalities describing relevant routine factors that impact health care delivery and medico-legal litigation are outlined with suggestions on how they may be effectively implemented. Conclusions: The improved knowledge of healthcare professionals on the up- to-date Clinical Guidelines along with the law of Land concerning medico Legal issues will be constructive in health service delivery by reducing the amount of litigation in Obstetrics and Gynecology. Appropriate use of informed consent, counseling, documentation and proper record keeping is a top priority. Telephone consultation and Telemedicine may attract various liability issues. Hospital administration policy of risk management including regular audits, near-miss investigation, mortality-morbidity discussions, and timely reviews of Clinical guidelines will help reduce litigation in these fields. Further research into medico-legal cases and policy making is a necessity. Keywords: Bolam, Bolitho, Medico legal, Montgomery, Prevention